Kerangka Rizobakteri Pemacu Pertumbuhan Tanaman, Ketahanan Sistemik Terinduksi, Dan Sumber–Serapan Dalam Pembentukan Mutu Buah Melon: Sebuah Uji Eksperimental - Budhi Haryanto; Ida Aryati Diyah Purnomo Wulan; Srie Juli Rachmawatie; M. Gunawan Setyadi; Didik Setyawan; Pramudya Ibnu Subrata (Jurnal Pertanian Khairun, 2025)
This study addresses the need to improve melon fruit quality while reducing dependence on chemical inputs by evaluating the effectiveness of a consortium based plant growth promoting rhizobacteria (PGPR) biofertilizer biopesticide. The objective was to assess its impact on the quality of Madesta melon grown in a lowland clay soil agroecosystem, focusing on fruit weight, netting density, and rind color. A two group experimental design (biological treatment versus control) was implemented using a polybag system under uniform basal NPK fertilization. One fruit per plant was evaluated at 75 days after anthesis. Data were analyzed using the Shapiro Wilk test for normality, Welch’s t test for mean comparisons with 95% confidence intervals, and complementary nonparametric tests for ordinal variables. The results showed that plants receiving the biofertilizer biopesticide consistently produced heavier fruits with denser netting and brighter, more uniform rind color than the control group, with statistically significant differences and large effect sizes. These findings indicate that PGPR based biofertilizer biopesticide application is an effective complementary strategy to enhance melon fruit quality and uniformity, with potential economic benefits and reduced chemical residue risks. Further multi location and multi season evaluations are recommended to support wider adoption.